The role of temporary mechanical circulatory support as a bridge to advanced heart failure therapies or recovery. (27th September 2022) - Oren, Daniel; Zilinyi, Robert; Lotan, Dor; Uriel, Matan; Uriel, Nir; Sayer, Gabriel
Abstract : Purpose of review: Temporary mechanical circulatory support (tMCS) has become central in the treatment of refractory cardiogenic shock and can be used to bridge patients to durable MCS, heart transplant or recovery. This review will discuss contemporary data regarding bridging strategies utilizing tMCS. Recent findings: There has been significant growth in tMCS use recently, driven by increased familiarity with tMCS devices, and increased experience with both implantation and management. Identifying goals of therapy at the time of therapy initiation can facilitate better outcomes. The three primary goals are bridge to recovery, bridge to heart transplantation or bridge to durable left ventricular assist device. Bridging to recovery requires adequate treatment of underlying conditions and optimization of haemodynamics. Bridging to heart transplantation has become more frequent following changes to the heart allocation policy. Despite early concerns, patients bridge with tMCS, including ventricular-arterial extracorporeal membrane oxygenation, do not appear to have worse posttransplant outcomes. When bridging to durable mechanical circulatory support, tMCS can be used to enhance end-organ dysfunction and improve perioperative outcomes. In situations in which none of these goals are attainable, palliative care plays a critical role to identify patient wishes and assist with withdrawal of care when necessary. Summary: The use of tMCS, as a bridge to recovery or heart replacement therapy in patients with refractory cardiogenic shock has grown significantly over the past decade. Multiple device choices are available and must be chosen appropriately to address the specific situation and the goals of therapy.